PENGARUH KREATIVITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA BPJS KETENAGAKERJAAN CABANG PEMATANGSIANTAR - Risma Nurhaini Munthe (Universitas Islam Sumatera Utara, 2019)
As for the problem in this research is how the creativity and quality of service towards the satisfaction of participants BPJS branch manpower Pematangsiantar. This research aims to know how to influence the creativity and quality of service towards the satisfaction of participants BPJS employment Branch Pematangsiantar.The data collection techniques in this study are with questionnaires, research and literature studies. The population in this research is the participants of BPJS employment who participated in JKK program during March-April 2017 and samples taken as many as 68 respondents using the strata random sampling. The analysis used include validity test, rehabilitation test, classical assumption test, multiple linear regression analysis, hypothesis test used test T, Test F, and coefficient of determination (R2) using SPSS support version 20.From the results of this study acquired double linear regression equation Y = 2,563 + 0, 202X1 + 0, 698X2 which means if the independent variables are considered constant then the participant satisfaction value (Y) increased 2,563%, when the creativity (X1) rose by 1 Satuanmaka Participant satisfaction will increase by 0.2012%, and if the quality of service (X2) rises by 1 unit then the satisfaction of participants will increase by 0.698%. Inopportune significantly influence between creativity to the satisfaction of participants demonstrated from the results of the Thitung test (2.772) This (1.668) with Signifikan0,007 0.05. And there is also a significant influence between creativity and quality of service to the satisfaction of participants is shown in Fcount (9.617) This 3.14 with a significant 0.000 0.05. With the value of R2 gained the magnitude of the influence of creativity and quality of service to the satisfaction of the participant sebesasddr 66.8% and the remaining 33.2% influenced by other variables outside this study.